3
$\begingroup$

This inequality has been given to me by my teacher to keep me occupied and after hours of fumbling around with it, and later trying to google it. I found nothing at all.

For any three positive real numbers $a$, $b$ and $c$, where $abc = 1$ and $a\le b \le c$, prove that:

$$(a+1)(c+1)>3.$$

$\endgroup$
  • $\begingroup$ Are you missing some assumptions like positivity? Otherwise take $a=-1,b=-1, c=1$ $\endgroup$ – lulu Sep 9 '17 at 21:42
  • 1
    $\begingroup$ @lulu he stated that they are $3$ positive real numbers !. $\endgroup$ – Ahmad Sep 9 '17 at 21:42
  • $\begingroup$ @Ahmad Ah, so he did. Thanks! Second problem today I have totally misread. $\endgroup$ – lulu Sep 9 '17 at 21:43
  • $\begingroup$ @lulu with such contribution to the site, you are entitled to make as many mistakes as they can count :) $\endgroup$ – Ahmad Sep 9 '17 at 21:47
  • $\begingroup$ @Ahmad Kind of you to say. $\endgroup$ – lulu Sep 9 '17 at 21:49
2
$\begingroup$

First simplify the expression :

$ac + a + c + 1 \gt 3 \iff ac + a+c \gt 2 \iff 1/b + a+ c \gt 2 \iff 1 + ab+bc \gt 2b $

We should prove $1+ab+bc \gt 2b$ . Use the condition $a\le b\le c $ :

$a\le b\le c \iff 2a \le a+b \le a+c \to a+b\le a+c$

From these we have :

$a+b\le a+c \iff ab + b^2 \le ab + bc \iff ab + b^2 +1 \le ab + bc+ 1$

If we prove $ab + b^2 +1 \gt 2b $ then problem is solved :

$ab + b^2 +1 \gt 2b \iff ab + (b-1)^2 \gt 0$

which is obvious because $ab \gt 0 $ and $(b-1)^2 \gt 0$

Done !

$\endgroup$
2
$\begingroup$

Since $b$ plays no role in the minimizing quantity, we might as well set $b=c$ to get the smallest $ac=\frac1b$. That means $$ ac^2=1\tag{1} $$ Using $(1)$, we want to find the minimum of $$ \begin{align} (a+1)(c+1) &=\left(\frac1{c^2}+1\right)(c+1)\\ &=c+1+\frac1c+\frac1{c^2}\tag{2} \end{align} $$ $(2)$ is minimized when $$ c^3-c-2=0\tag{3} $$ The real root of $(3)$ is $$ c=1.521379706805\tag{4} $$ Plugging $(4)$ into $(2)$ says that the minimum is $$ (a+1)(c+1)\ge3.610718613276\tag{5} $$

$\endgroup$
  • $\begingroup$ very nice (+1), also will delete my post,thanks. $\endgroup$ – Ahmad Sep 9 '17 at 22:57
  • $\begingroup$ Thanks, but where does $c^3-c-2=0$ come from? $\endgroup$ – Vfdking Sep 9 '17 at 23:14
  • $\begingroup$ @Vfdking: taking the derivative of $(2)$. $\endgroup$ – robjohn Sep 10 '17 at 2:10
1
$\begingroup$

Our conditions give $c\geq1$ and $c\geq b$.

Thus, by AM-GM we obtain: $$(a+1)(c+1)=ac+a+3\cdot\frac{c}{3}+1\geq5\sqrt[5]{ac\cdot a\cdot\left(\frac{c}{3}\right)^3}+1=$$ $$=\frac{5}{\sqrt[5]{27}}\sqrt[5]{a^2c^4}+1\geq\frac{5}{\sqrt[5]{27}}\sqrt[5]{a^2b^2c^2}+1=\frac{5}{\sqrt[5]{27}}+1>3.$$ Done!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.